PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA MENGGUNAKAN MODEL PEMBELAJARAN BERDASARKAN MASALAH UNTUK MEMFASILITASI KEMAMPUAN REPRESENTASI MATEMATIS PESERTA DIDIK SMP/MTs - Dhea Dwi Jayantis; Maimunah Maimunah; Kartini Kartini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research was conducted due to limited mathematics learning instruments to facilitate mathematical representation ability students. This research aims to produce mathematic learning instruments like lesson plan (LP) and student worksheet (SW) by Problem Based Learning (PBL) to facilitate mathematical representation ability on Linier Equation System of Two Variables for 8th grade which valid and practicality. Development model used is 4-D model that consist of define, design, development and disseminate, but disseminate didn’t do because this purpose of study just produce LP and SW which valid and practicality and got it on development step. LP and SW compiled was validated by three validators and revised based on the suggestions of validators. Based on the result of data analysis shows average score for LP are 3.88 and for SW are 3.82. LP and SW was categorized as very valid. SW was valeted are conducted two trials for a small group on 9 students of 9th grade MTs Darul Hikmah Pekanbaru and a large group on 21 students of class VIII.A3 MTs Darul Hikmah Pekanbaru. The result of average score SW for small group are 95,92% was categorized as very practical and for large group are 94,84% was also categorized as very practical..Key Words: Validity and Practicality, Problem Based Learning,Mathematical Representation Ability